(untitled) (Bangladesh Journal of Medical Science, 2022)
Aim: The study was completed with a descriptive design with the aim of determining the effect of preoperative stress on pain beliefs and used a relationship seeking design with the aim of revealing whether there is a significant correlation between pain beliefs and surgery anxiety levels among patients about to undergo surgical procedures in the urology clinic. Material and method: With descriptive and relationship seeking type, the study was completed with 112 patients admitted to the urology clinic for surgical procedures. For collection of data, a personal information form, pain beliefs scale and preoperative anxiety scale were used. Results: The majority of volunteers participating in the research were male (62.5), married (74.1%), aged 51 years or older (56.3%), primary school graduates (28.6%) and retired (38.4%) with moderate income levels (48.2%). Most patients had spinal anesthesia (48.1%) administered. There was a significant difference found between the surgery anxiety levels and pain beliefs with the anesthesia type administered. There was a negative, low power and statistically very advanced correlation between surgery anxiety and pain beliefs (r: -0.445; p˂0.05). Additionally, among the pain belief subdimensions psychological beliefs were mostly correlated with surgery anxiety ( r: -0.546; p˂0.05) Conclusion: The research found a correlation between anxiety levels and pain beliefs of patients and concluded that researching this in different samples and nurses assessing the pain beliefs of patients will reduce anxiety. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 271-278